Three views on the New Testament use of the Old Testament - Berding, Kenneth; Lunde, Jonathan, 1960-; Kaiser, Walter C; Bock, Darrell L; Enns, Peter (Grand Rapids, MI Zondervan, 2008)
To read the New Testament is to meet the Old Testament at every turn. But exactly how do Old Testament texts relate to their New Testament references and allusions? Moreover, what fruitful interpretive methods do New Testament texts demonstrate? Leading biblical scholars Walter Kaiser, Darrel Bock and Peter Enns each present their answers to questions surrounding the use of the Old Testament in the New Testament. Contributors address elements such as Divine and human authorial intent, the context of Old Testament references, and theological grounds for an interpretive method. Each author applies his framework to specific texts so that readers can see how their methods work out in practice. Each contributor also receives a thorough critique from the other two authors. A one-stop reference for setting the scene and presenting approaches to the topic that respect the biblical text, Three Views on the New Testament Use of Old Testament gives readers the tools they need to develop their own views on this important subject. - Publisher.
An introduction to the central questions ... / Jonathan Lunde -- Single meaning, unified referents / Walter C. Kaiser, Jr. ; Responses -- Single meaning, multiple contexts and referents / Darrell L. Bock ; Responses -- Fuller meaning, single goal / Peter Enns ; Responses -- An analysis of the three views ... / Kenneth Berding.
Includes indexes.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Relation to the Old Testament